2019
DOI: 10.2217/fon-2019-0102
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic Features of Pneumonitis Associated With Nivolumab in Non-Small-Cell Lung Cancer and Malignant Melanoma

Abstract: Aim: To assess the clinical features/imaging characteristics of pneumonitis reported during nationwide nivolumab postmarketing surveillance in Japan. Patients & methods: Clinical and radiological data were collected from pneumonitis cases reported during/after nivolumab treatment for melanoma or non-small-cell lung cancer. The expert central review committee evaluated each case. Results: Among 144 cases analyzed, 91 (63.2%) had radiological patterns considered typical for drug-induced pneumonitis and 53 (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 20 publications
6
57
0
3
Order By: Relevance
“…Although it is difficult to distinguish between the two forms of pneumonitis, ICI-related pneumonitis has been reported to exhibit some specific radiological features, such as ground glass opacities (GGOs), a cryptogenic organizing pneumonia-like appearance, and interstitial pneumonia pattern [18]. Baba T et al [19] reported that GGOs around the tumor (peritumoral infiltration) were a characteristic finding in pneumonitis induced by nivolumab.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is difficult to distinguish between the two forms of pneumonitis, ICI-related pneumonitis has been reported to exhibit some specific radiological features, such as ground glass opacities (GGOs), a cryptogenic organizing pneumonia-like appearance, and interstitial pneumonia pattern [18]. Baba T et al [19] reported that GGOs around the tumor (peritumoral infiltration) were a characteristic finding in pneumonitis induced by nivolumab.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 ICI-ILD often occurs earlier in lung cancer, with a median of 2.1 months after ICI treatments, 1 and presents as several radiologic patterns. 18 A total of 70-80% of ICI-ILD cases can be controlled through the prompt initiation of a high dose of steroids. 19 In our case, the male patient had a long history of smoking and his chest CT showed severe pre-existing interstitial lung disease, which might lead to the occurrence of ILD after 15 cycles of nivolumab treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Some case reports have reported the acute exacerbation of underlying infection, such as pulmonary tuberculosis, during anti-PD-1 antibody therapy. [20][21][22] Retrospective studies also demonstrated increased risk of infection in patients receiving ICIs along with immunosuppressive agents, including corticosteroids and infliximab, as well as in patients with concomitant diabetes mellitus. 23 24 However, because the subjects with underlying infection, uncontrolled diabetes mellitus or the concomitant use of immunosuppressive agents were excluded based on the exclusion criteria of each phase I study, these events were not recorded in our study.…”
Section: Discussionmentioning
confidence: 99%